Corporate identity and internal implementation of a corporate brand - Koskimies, Virpi (2011)
Companies cannot build their strategy on predictable markets anymore ‐ all organizations nowadays need to adapt to change. In the heart of the change lies organizations identity. Corporate identity is closely related to corporate branding. This study focuses on a situation of change in a company with multiple identities. The case organization used to operate under several product and company brands that were merged into one and began building a coherent corporate brand.